Analysis functional in individuals with backache occupational low back pain (Research, Society and Development, 2021)
Occupational low back pain is a problem that affects workers who remain seated for long hours, mainly affecting those of working age. Objective: to analyze the functionality of individuals with occupational low back pain. Methodology: this is a case study, descriptive and quantitative, which was carried out with 6 individuals of both genders, aged between 25 and 50 years, using the visual analogue scale, Nordic musculoskeletal symptoms questionnaire, Roland-Morris questionnaire and physical therapy assessment. Results: the mean age was 31.83±9.04, the visual analogue scale had a mean of 4.67±1.63. 83.33% had some problem in the last 12 months and 66.67% had low back pain in the last 7 days. The Roland Morris questionnaire obtained a score of 2.33±2.42 in the range of motion analysis for flexion, it was possible to observe an average of 86.67±9.83, in relation to the extension amplitude the average was 26.67±5.16. When the degree of muscle strength for the flexor muscles is analyzed, an average of 3.83±0.98 is observed, while the extensor muscles have an average of 26.67±5.16. Conclusion: occupational low back pain is directly linked to sitting and causes pain, muscle weakness and shortening, thus altering its functionality.